Seasonal movements, migration and age determination of Burchell's Zebra (Equus burchelli antiquorum, H. Smith, 1841) in the Kruger National Park - Eloff, F.C. (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1972.